Steroid-sparing effect of anakinra in giant-cell arteritis: a case series with clinical, biological and iconographic long-term assessments. (20th March 2021) - Deshayes, Samuel; Ly, Kim-Heang; Rieu, Virginie; Maigné, Gwénola; Martin Silva, Nicolas; Manrique, Alain; Monteil, Jacques; de Boysson, Hubert; Aouba, Achille; ,
Abstract: Objectives: The treatment of GCA relies on corticosteroids but is burdened by a high rate of relapses and adverse effects. Anti-IL-6 treatments show a clear benefit with a significant steroid-sparing effect, but late relapses occur after treatment discontinuation. In addition to IL-6, IL-1 also appears to play a significant role in GCA pathophysiology. We report herein the efficacy of anakinra, an IL-1 receptor antagonist, in six GCA patients exhibiting corticosteroid dependence or resistance, specifically analysing the outcome of aortitis in four of them. Methods: This retrospective study analysed the cases of all GCA patients treated with anakinra from the French Study Group for Large Vessel Vasculitis. Results: After a median duration of anakinra therapy of 19 (18–32) months, all six patients exhibited complete clinical and biological remission. Among the four patients with large-vessel involvement, one had a disappearance of aortitis under anakinra and three showed a decrease in vascular uptake. After a median follow-up of 56 (48–63) months, corticosteroids were discontinued in four patients, and corticosteroid dosage could be decreased to 5 mg/day in two patients. One patient relapsed 13 months after anakinra introduction in the context of increasing the daily anakinra injection interval to every 48 h. Three patients experienced transient injection-site reactions, and one patient had pneumonia. Conclusion: In this short series, anakinra appears to be an efficient and safe steroid-sparing agent in refractory GCA, with a possible beneficial effect on large-vessel involvement.